Pengelolaan Akun Instagram CEO Telkomsel @hendrisjam - Evi Cristiana; Anisa Diniati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
Building a positive company reputation can be done by company's CEO using social media. This research aims to understand how Telkomsel implements CEO communication as public relations strategy in managing CEO Telkomsel @hendrisjam's Instagram account. This research uses the Public Relations Strategy theory by Cutlip Center (2013). This research used qualitative approach with descriptive research and data collection techniques which were conducted through in-depth interviews with one key informant, two expert informants, and four supporting informants, also through non-participant observation and document study. Based on the research results, it was found that Telkomsel's public relations implemented a special strategy in managing their CEO's Instagram account which consisted of five stages, such as secondary analysis for new innovations, setting more specific activity goals, determining target audiences, strengthening HR expertise to implement activity planning, and program evaluation. The final conclusion is that Telkomsel's positive reputation can be built through personal branding that the CEO communicates on Instagram according to the goals of this activity, and the perception tone obtained from followers is also positive.